Nanoseparation Using Density Gradient Ultracentrifugation Mechanism, Methods and Applications - Sun, Xiaoming; Luo, Liang; Kuang, Yun.; Li, Pengsong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book introduces the classification and mechanism of density gradient ultracentrifugation (DGUC) method with rich examples showing the versatility of such an efficient separation technique. It also gives a strict mathematical description and a computational optimization model to predict the best separation parameters for a given colloidal system. The concept of "Lab in a tube" is proposed in the last chapter, which allows the size-property relationship investigation, synthetic optimization and reaction/assembly mechanism exploration etc. .
Keywords: Nanotechnology; Analytical chemistry; Polymers; Nanochemistry; Inorganic chemistry; Nanotechnology; Analytical Chemistry; Polymers; Nanochemistry; Inorganic Chemistry